Heteronormativity and the Justification of Gender Hierarchy: Investigating the Archival Data From 16 European Countries - Ferrari, Federico; Imperato, Chiara; Mancini, Tiziana (Frontiers in Psychology, 2021)
Within the framework of the System Justification Theory, this study tested on the archival data from 16 European countries the general hypothesis that homonegativity (HN), as an expression of gender binarism and heteronormativity, works as a legitimizing myth of gender hierarchy. Specifically, we hypothesized that (1) system justification (SJ) would positively relate to HN and (2) this relation would depend on the country level of gender hierarchy, (3) on the gender of respondents, and (4) on the interaction between gender hierarchy and gender. We selected the Gender Equality Index (GEI) as an indicator of the gender hierarchy of the country system and the items from the European Social Survey-Round 9 (ESS-9) as the indicators of the gender of respondents and the levels of SJ and HN. The Hierarchical Linear Modeling (HLM) partially confirmed the hypotheses, suggesting HN to work as a blatant prejudice and being more viable as a legitimizing myth in females from countries with higher gender hierarchy and in males from more gender-equal countries. In both cases, HN serves as a myth to justify the ontological premise of participants that the world is fair and to counteract the cognitive dissonance generated by the perception of a gender-unequal system (in the case of a woman) or by the perception of a gender-equal system that can threaten gender privileges (in the case of a man).